The role of colony morphotype in shaping gene essentiality in Mycobacteroides abscessus - Brittany N. Ross; Emma Evans; Frances Diggle; Paul Briaud; Marvin Whiteley (Proceedings of the National Academy of Sciences, 2025)
Changes in bacterial colony morphology are common during chronic human infections and are thought to provide a survival advantage. In the human pathogen Mycobacteroides abscessus (MAB), a unidirectional transition from a smooth (MAB S ) to rough (MAB R ) morphotype frequently occurs during chronic infection. This transition has profound clinical implications, as MAB R induces a heightened proinflammatory response, contributing to increased morbidity. To better understand this phenomenon, we used transposon insertion site sequencing (Tn-seq) to identify genes essential for the survival of MAB S and MAB R . Our analysis revealed distinct genetic requirements for growth in vitro, including several genes involved in responding to environmental stresses. Notably, some of these uniquely essential genes are therapeutic targets in mycobacteria. In a murine infection model, the divergence in essential gene profiles between MAB S and MAB R was even more pronounced, driven partly by the differing host immune responses elicited by each morphotype. These findings demonstrate that the transition from a smooth to rough morphotype not only impacts MAB’s survival strategies but also highlights the importance of considering morphotype-specific genetic and functional adaptations when developing therapeutic approaches. Our work underscores the critical need to incorporate morphotype conversion into the prioritization of drug targets, as targeting morphotype-specific vulnerabilities could improve treatment outcomes for infections caused by this pathogen.